1980
DOI: 10.1159/000459271
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Liver Gamma-Glutamyl Transferase in Chronic Alcoholics

Abstract: The activity of γ-glutamyl transferase (γ-GT) in the liver of 36 chronic alcoholics was twice as high as in the control group. The elevation was of the same order in cases with and without hepatic lesions. However, the activity of γ-GT in the sera of alcoholic patients with chronic hepatitis and liver cirrhosis was significantly higher than in the remaining alcoholics. There was no correlation between the enzyme activities in the liver and in the serum of the patients examined. Consequently, the determination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1983
1983
1991
1991

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Early reference standards were developed in alcoholic and heavy-drinking populations, and there appears to be marked individual variation in the response to GGT to varying levels of alcohol consumption. It is also not clear whether or not GGT returns to normal after even a year of abstinence from alcohol [Belfarge et al, 1977;Robinson et al, 1979;Ivanov et al, 1980;Kristenson et al, 1981;Papoz et al, 19811. Diseases associated with elevated GGT include pancreatitis, hepatitis, obstructive jaundice, intrahepatic cholestasis, cancer of the pancreas, acute myocardial infarction, and renal disease [Hardison, 19791. Recent investigations of the presence and role of GGT in skin have shown that it is an important enzyme in keratinization.…”
Section: Discussionmentioning
confidence: 99%
“…Early reference standards were developed in alcoholic and heavy-drinking populations, and there appears to be marked individual variation in the response to GGT to varying levels of alcohol consumption. It is also not clear whether or not GGT returns to normal after even a year of abstinence from alcohol [Belfarge et al, 1977;Robinson et al, 1979;Ivanov et al, 1980;Kristenson et al, 1981;Papoz et al, 19811. Diseases associated with elevated GGT include pancreatitis, hepatitis, obstructive jaundice, intrahepatic cholestasis, cancer of the pancreas, acute myocardial infarction, and renal disease [Hardison, 19791. Recent investigations of the presence and role of GGT in skin have shown that it is an important enzyme in keratinization.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that high serum y-gluta myltransferase [(5-glutamyl)-peptide amino acid 5-glutamyltransferase; EC 2.3.2.2] activ ities are frequently associated with alcohol ism [18], and it has been reported that this measurement is the best single indicator of liver involvement in chronic alcoholism [6], Increased y-glutamyltransferase activity in the liver tissue itself was first reported in patients with alcoholic liver disease by Sey mour et al [21] and Seymour and Peters [22,23] and subsequently confirmed by other workers [10,16,20,28]. This increase in hepatic activity has also been found in rats following chronic alcohol consumption [5, 7-9, 12-15, 24, 27-29],…”
Section: Introductionmentioning
confidence: 84%
“…Seymour and Peters [15] reported that ele vated GGT activity was more strongly mani fested in cases with liver cirrhosis. On the other hand, Ivanov et al [16] also reported that enhanced hepatic GGT activity did not adequately reflect the severity of hepatic damage, and there was no correlation be titis, and the area of newly formed fibrosis in precursor of collagen, may be increased in the cirrhosis showed prominent GGT activity, course of enhanced GGT activity, it is possiOn the other hand, Takebayashi et al [18] ble that the enhanced hepatic GGT activity reported that sufficient GGT activity was in chronic alcoholics could contribute to the demonstrated in the cytoplasm of liver cells, pathogenesis of liver fibrosis [21], Our results the cell membranes adjacent to the lumen of support this hypothesis, bile canaliculi and along pericellular fibers around the balloon-shaped liver cells in alco holic hepatitis.…”
Section: Discussionmentioning
confidence: 99%